Change in Surface Roughness of Esthetic Restorative Materials after Exposure to Different Immersion Regimes in a Cola Drink. (23rd March 2014) - Bajwa, Navroop Kaur; Pathak, Anuradha
Abstract : Context . An in vitro study carried out to evaluate and compare the effect of Cola drink on surface roughness of esthetic restorative materials. Purpose . To compare the effect of different immersion regimes in a Cola drink on surface roughness of esthetic restorative materials. Method . Two hundred samples were grouped into 4 equal groups of 50 samples each: Group I : conventional glass ionomer, Group II : resin modified glass ionomer, Group III : polyacid-modified resin composite, Group IV : Composite resin. Each group was further subdivided into 5 subgroups of 10 samples each. Subgroup A (Control Subgroup) . Samples were kept immersed in artificial saliva. Subgroup B . Samples were immersed in Cola drink once a day. Subgroup C . Samples were immersed in Cola drink, 3 times a day. Subgroup D . Samples were immersed in Cola drink 5 times a day. Subgroup E . Samples were immersed in Cola drink 10 times a day. Each immersion lasted 5 minutes. The immersion protocol was repeated for 7 days. Results . Maximum surface roughness was seen in Group I conventional glass ionomer cement, followed by Group II resin modified glass ionomer, Group III polyacid modified resin composite, and Group IV composite resin samples. Conclusion . Resistance to change in surface roughness is more in resin based restorative materials as compared to glass ionomer based materials.